The assessment of indicator of bone metabolism (IBM) and establishing the range of its normal values in healthy women and men - Tryniszewski, Wiesław; Sobczuk, Anna; Górska-Chrząstek, Magdalena; Gadzicki, Mariusz; Raciborska, Iwona; Zając, Andrzej; Maziarz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2011)
Introduction: Bone mass and metabolism undergo different changes with age. Osteoporosis is an important problem for both men and women. The assessment of bone metabolism includes bone mineral density and quality. Several years of experience with our own method of bone scintigraphy allowed us to determine IBM and its range of normal values in men and women. Aim: To establish IBM and define its range of normal values in healthy men and women. To compare IBM and BMD and their possible use in the skeletal system assessment. Material and methods: 117 healthy women and 90 healthy men underwent the assessment: anthropometric, biochemical, hormonal, vascular and densitometric examinations using the DXA technique. IBM establishing and its normal range of values in men and women. Results: Normal results of anthropometric, biochemical, hormonal, vascular and densitometric examinations exclude osteoporosis. The range of IBM normal values was comparable in men and women. In men, the minimal value of IBM was slightly higher than in women. The study allowed us to determine the normal range of IBM values. In men, a wider range of normal IBM values was observed. Conclusions: Our own program and method allowed us to establish a bone metabolism indicator and its normal range of values in healthy men and women. It was observed that the speed of bone changes in men and women was similar, yet, IBM values in men were slightly higher. IBM along with densitometry completes the skeletal system diagnostics in healthy patients, in osteoporosis and other pathological conditions.